The Effectiveness of Entrepreneurship Mentoring in Developing Perfume-Making Hard Skills Among MSME Groups - Arvenia Fortuna B; Satrio Aji P; Dede Purwanti; Ladilyono Ladilyono; Achmad Agus Yasin Fadli; Mukhlis Chatio (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This community service activity is entitled